Adaptation and validation of the Hindi mini tinnitus questionnaire - Semwal, Abhishek; Khemka , Srabanti (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2026)
Background: Tinnitus, the perception of sound without an external source, can significantly affect an individual’s psychological well-being. However, tools for assessing tinnitus-related distress in the Hindi-speaking adults remain limited. This study aimed to translate, culturally adapt, and validate the mini tinnitus questionnaire (Mini-TQ) into Hindi (MiniTQ-H). Methods: The Hindi translation of the original Mini-TQ was conducted following standardized guidelines. The study included 60 individuals, comprising of two groups: normal hearing sensitivity with tinnitus (NWT) (n=30) and hearing impairment with tinnitus (HWT) (n=30). Psychometric evaluation of the Hindi MiniTQ was performed, including assessments of internal consistency, test-retest reliability, criterion validity, and concurrent validity. Sensitivity and specificity of the MiniTQ Hindi version were determined using receiver operating characteristic (ROC) curve analysis. Results: The MiniTQ-H demonstrated excellent psychometric properties. Content validity was confirmed by expert panel consensus, criterion validity demonstrated very strong agreement and Cronbach’s alpha for internal consistency was 0.822, indicating good reliability. Test-retest reliability was high, with all items maintaining significant correlations over time. MiniTQ-H showed a strong concurrent validity with THI-H. ROC analysis yielded a cut-off score of 14.5 with high score of 24, demonstrating high diagnostic accuracy in identifying individuals with tinnitus-related distress. Conclusions: The MiniTQ-H is a culturally and linguistically appropriate tool for assessing tinnitus-related distress in Hindi-speaking individuals aged 18 to 60 years. It provides a reliable and valid measure for clinical and research use in India.